THE EFFECT OF AIUEO AND BLOWING-PIPE SPEECH THERAPY ON VERBAL COMMUNICATION DISORDERS IN STROKE PATIENTS: CASE REPORT - Insani, Inas Nur; Upoyo, Arif Setyo; Taufik, Agis (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Introduction: Stroke is an acute clinical event in the form of a focal or global neurological disorder associated with cerebral circulation disorders that lasts more than 24 hours resulting in death without a known cause other than originating from the blood vessels. One therapy that can be given to stroke sufferers who experience speech disorders is speech therapy. Purpose: This case study aims to determine the effect of AIUEO speech therapy and blowing pipe therapy on verbal communication disorders in stroke patients. Methods: Implementation based on Evidence-based Nursing (EBN) refers to PICO by searching for related articles and journals from 2019-2023 using Google Scholar and it was found that AIUEO speech therapy and blowing-pipe are references that can be used for nursing interventions. AIUEO speech therapy intervention combined with blowing-pipe therapy was carried out one morning and one evening for 5 days. Evaluation of the results of the implementation of the therapy provided using Tikofsky's 50 Word Intelligibility Test instrument which was measured before and after therapy was given for 5 consecutive days. Keywords used: AIUEO speech therapy, blowing-pipe therapy, verbal communication disorders. Discussion: The evaluation results showed that there was a decrease in verbal communication disorders as evidenced by an increase in Tikofsky's 50 Word Intelligibility Test score from 48 to 66. This shows that the patient was able to pronounce more words clearly. Conclusion: There was a reduction in verbal communication disorders in patients after being given AIUEO speech therapy intervention and blowing pipe therapy.